Efectividad de la estrategia de recursos humanos: modelo integrador de la Teoría de Recursos y Capacidades y la Teoría del Comportamiento en las entidades financieras de la economia social - Hernández Perlines, Felipe; Peña García-pardo, Isidro (REVESCO. Revista de Estudios Cooperativos, 2008)
This work places in the line of investigation that analyzes the relation between the strategy of human resources and the results. In I make concrete, we will propose an integration model of the principal theoretical perspectives that have served to articulate the empirical investigation: a) Theory of Resources and Capacities - based principally on the creation on the part of the company of the human capital, which is constituted in the base for the attainment of competitive advantages; and b) Theory of the Behavior - while so much that the improvement of the results besides a highly formed and qualified workforce, needs that certain behaviors and attitudes demonstrate.